Morphometric study of the differentiation in Acacia bonariensis and Acacia caven var. caven (Fabaceae) in two biological reserves - Rajngewerc, Lucila (2021)
Background and aims: The genus Acacia has a pantropical distribution and currently consists in approximately 1.450 species throughout the world. In Argentina the species belong to two subgenera: Acacia and Aculeiferum. In this work the morphology of two species was studied, one belonging to the first subgenus, Acacia caven var. caven and Acacia bonariensis, corresponding to the second one. The aim of this study was to evaluate the interspecific and intraspecific variation based on 12 exomorphological traits. The hypothesis was that the selected traits were able to differentiate species and populations. M&M: The study was based on the Kruskal Wallis test and several analyses with multivariate methods. Results: The Kruskal Wallis test found that nine characters were able to differentiate the species and one the populations. From the multivariate analyses the result was that, except for one character, the remaining ones were significant for the interspecific differentiation. Conclusions: This showed a clear separation between species according to the taxonomic classification already established. However, no differences between reserves could be evidenced for either of the species with these methods. In conclusion, these analyses set a precedent for future studies including more natural populations and the genetic study of the differentiation at molecular level.